Purification and molecular docking study of a novel angiotensin-I converting enzyme (ACE) inhibitory peptide from alcalase hydrolysate of ultrasonic-pretreated silkworm pupa (Bombyx mori) protein. Issue 5 (May 2015) - Jia, Junqiang; Wu, Qiongying; Yan, Hui; Gui, Zhongzheng
Graphical abstract